Clinical correlates of seasonality in bipolar disorder: A specifier that needs specification?. (25th December 2020) - Fico, Giovanna; de Toffol, Marco; Anmella, Gerard; Sagué‐Vilavella, Maria; Dellink, Annelies; Verdolini, Norma; Pacchiarotti, Isabella; Goikolea, Jose Manuel; Solmi, Marco; Vieta, Eduard; Murru, Andrea
Abstract: Objective: Seasonal pattern (SP) is a bipolar disorder (BD) specifier that indicates a tendency towards affective relapses during specific moments of the year. SP affects 15%–25% of BD patients. In the past, SP was applied only to depressive relapses while, in DSM‐5, SP may be applied to both depressive and (hypo)manic episodes. We examined the association between different clinical correlates of BD and SP according to its current definition in a cohort of patients with BD type I (BDI) and II (BDII). Methods: Patients were recruited from a specialized unit and assessed according to the season of relapse and type of episode per season. SP and non‐SP patients were compared looking into sociodemographic and clinical correlates. Significant variables at univariate comparisons were included in multivariate logistic regression with SP as the dependent variable. Results: 708 patients were enrolled (503 BDI, 205 BDII), and 117 (16.5%) fulfilled DSM‐5 criteria for SP. The mean age was 45.3 years (SD = 14.18), and 389 were female (54.9%). The logistic regression model included a significant contribution of BDII (OR = 2.23, CI 1.4–3.55), family history of mood disorder (OR = 1.97, CI 1.29–3.01), undetermined predominant polarity (OR = 0.44, CI 0.28–0.70), and aggressive behavior (OR = 0.42, CI 0.23–0.75). Conclusion: Our results outline a novel positive association of SP with undetermined predominant polarity, BDII, family history of mood disorder, and with fewer aggressiveness‐related symptoms. Seasonality is associated with a biphasic pattern with similar dominance of (hypo)mania and depression and is more frequent in BDII as compared to BDI. Seasonal episodes may be easier to predict, but difficult to prevent.